(untitled) (Academicia Globe: Inderscience Research, 2023)
The article compares the changes in the soil of the area where Phytomeliorant plant Licorice is planted with the area where Licorice is not planted and the corresponding conclusions are made on this basis. Differences in soil environment, nutrient supply, micro and macro elements of licorice planted area were compared